Pré-nupcial Pastoral advice: A Preventive Proposal to Divorse - Sanches, Samuel (Vox Scripturae - Revista Teológica Internacional, 2025)
This article discusses the theme of the pre-nuptial preparation of couples as a preventive action to divorce. In this sense, it examines the question of new families and marriage in the present, Crisis-generating factors and divorce, as well as presenting a proposal for pre-nuptial educational counseling to prevent divorce. It is relevant research for churches and pastoral counselors, at a time when relationships are viewed as fluids. The results indicate a program of preventive educational pastoral counseling for spouses should have as horizons themes such as: 1) what is conjugality? 2) Emotional dependence 3) Orientations on sexuality 4) The role of finances in married life 5) Raising children 6) Infidelity in the virtual world. The research is theoretical, of a qualitative nature supported by bibliographic analysis.
Keywords: Counseling; Crisis; Divorce; Family; Preventive Action